Knowledge About Dental Caries Using Dental Monopoly Media In 4Th And 5Th Grade Students of SDN Bulu Kec. Sugihwaras Bojonegoro - Janah, Miftakhul; Hidayati, Sri; Prasetyowati, Silvia (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Dental health in school-age children, especially at the primary school level, has a very important role. The most common dental health problem experienced by children at an early age is dental caries. This caries can cause teeth to become brittle, perforated, and even broken, so that it can hamper the optimal growth of children. Problem statement: Based on preliminary data at SDN Bulu, as many as 8 out of students (80%) had dental caries. The problem in this study is the high percentage of caries in 4th and 5th grade students of SDN Bulu, the level of student knowledge about dental caries in 2025. Method: This type of research is descriptive research. With the number of respondents as many as 36 students. The measuring instrument used was a questionnaire sheet to see students' knowledge about dental caries. The data analysis technique used in this study was to calculate the average answers from all 4th and 5th grade students of SDN Bulu then percented and presented in tabular form. Results: The results showed that the knowledge of 4th and 5th grade students of SDN Bulu was in the good category. Conclusion: The level of knowledge of 4th and 5th grade students of SDN Bulu after counseling was 88%, including in the good category.